2022
DOI: 10.3390/min12121488
|View full text |Cite
|
Sign up to set email alerts
|

Static Liquefaction Causes the Flow Failure of a Tailings Dam: A Case Study of El Descargador, Cartagena–La Unión Mining Region, SE Spain (October 1963)

Abstract: The aim of this work is to investigate the causes of the El Descargador tailings dam failure, at the mine district Cartagena–La Unión (SE Spain), in October 1963. Dam stability back analyses have been carried out by applying a geotechnical and geophysical approach. The failure occurred in the form of several landslides in five different points along the dam structure. The rise in the pore pressure and the steeped slopes of the tails, scaling up to 40° in some sectors, were the main causal preparatory factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Mine wastes also play a particular role in this context because they represent a source of contamination. The pollution of soil and water by mining deposits has negative effects on both agricultural and tourism land uses; thus, a correct environmental characterization of the affected area is important for any proposal of effective measures that could help to minimize environmental impact and concern [4][5][6][7][8][9][10][11][12][13][14][15][16]. In November 2015, an iron mining tailing dam owned by Samarco Company collapsed in Brazil, releasing an estimated 52 million m 3 of tailings into the environment, affecting the public water supply, which was interrupted for a few weeks, to approximately 400,000 people, as well as industrial activities, electricity generation in three hydroelectric plants, fishing, tourism, and agriculture [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Mine wastes also play a particular role in this context because they represent a source of contamination. The pollution of soil and water by mining deposits has negative effects on both agricultural and tourism land uses; thus, a correct environmental characterization of the affected area is important for any proposal of effective measures that could help to minimize environmental impact and concern [4][5][6][7][8][9][10][11][12][13][14][15][16]. In November 2015, an iron mining tailing dam owned by Samarco Company collapsed in Brazil, releasing an estimated 52 million m 3 of tailings into the environment, affecting the public water supply, which was interrupted for a few weeks, to approximately 400,000 people, as well as industrial activities, electricity generation in three hydroelectric plants, fishing, tourism, and agriculture [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The rainy season exhibits a high incidence of geological slope disasters. Geological slope disasters such as debris flows and landslides are readily formed, especially under continuous rainfall [1][2][3][4]. Research has shown that in the rainfall seepage process, the rock and soil mass bulk density and the pore water pressure increase, the sliding force of the slope body increases, and the shear strength decreases, resulting in slope failure [5,6].…”
Section: Introductionmentioning
confidence: 99%